Euro 2012, the 'civilizational leap' and the 'supporters United' programme: a football mega-event and the evolution of fan culture in Poland. (4th July 2019) - Kossakowski, Radosław
ABSTRACT: The objective of this article is to evaluate the social and cultural significance of the 'Supporters United' programme, an unprecedented initiative combining fan culture, institutional actors and local authorities. The idea of this initiative was born during the preparation for Euro 2012 – first Mega Sport Event which Poland had organized since the system transformation in 1989. The organization of the European Championship was a milestone in the implementation of fan projects in Poland. The article discusses various activities undertaken by supporter centers, which provide evidence of the 'civilizing' evolution of fan culture. Importantly, such terms as 'civilizational leap' dominated Polish public discourse in the context of Euro 2012. Although the event generated infrastructural rather than social changes in Poland, the implementation of 'Supporters United' is its important legacy. This article also considers future possibilities for the development of fan initiatives in Poland.